Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam